Modeling of groundwater dynamics and the impact of development scenarios at Sarir wellfield - Salem Elsakran; Salma Abdallah; Fatima Ahmed (The Libyan Journal of Science, 2024)
The study area (Sarir field) is part of the man-made river project (MMRP) in Libya. The wellfield includes 126 production wells aligned on three parallel east-west lines, 1.3 km between the wells on each line, 10km between the three lines and includes over 24 exploratory and piezometric wells. The wellfield has two relatively separated aquifer systems: a shallow unconfined aquifer of Post Middle Miocene age and a deep semi-confined aquifer of the Middle Miocene age; both are composed of multi-layered sand, silt, shale, siltstone, and clay. The study aims to construct a Three-dimensional numerical model using finite difference method to simulate deferent development scenarios of the wellfield. Processing Modflow for Windows (PMWIN) had been used to construct, calibrate, optimize production, calculate budget and predict the drawdown of various development scenarios. At present, the Sarir well field produces approximately 600,000 m3/day and is planned to produce 1,000,000 m3/day in the future. The subsea depth to the top of the main aquifer is around 220 m, and the main aquifer thickness is around 250 m. A very good record of groundwater levels and water production data since it started on 1/1/1999 and up to 30/8/2005 is available for transient calibration. 140 boreholes have been used in the model and checked as active to benefit from most of the available data. A steady-state calibration has been performed against very well defined drilling information. A very good match between the simulated and the initially specified heads has been achieved. The transient simulated time is 2400 days, including 40 stress periods, during which the wellfield produced 714910755 m3, where a reasonable match between the measured and calculated water heads has been attained in the majority of the piezometer's hydrographs. Three operation scenarios with differing locations of the planned new wells have been made; the best was the second one, in which the new wells are along the three well field lines since it has the lowest maximum drawdown recorded (25 m) and the least reduction in storage (128000 m3). For the sake of additional assessment, additional model calibration is needed, to benefit from a large number of piezometers and exploratory wells available; this can only be attained if the water levels and production rates in the wellfield are recorded in smaller and more regular time intervals.